2008
DOI: 10.1111/j.1365-2621.2007.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of methanolic extracts from different parts of Sclerocarya birrea

Abstract: The methanolic extracts from Sclerocarya birrea leaves (SCL), roots (SCR), barks (SCB), and kernel oil cake (SCK) were examined for radical scavenging capacities and antioxidant activities. The total phenolics of the extracts was determined spectrophotometrically according to the Folin-Ciocalteau method using gallic acid as standard solution. The total phenolic compounds were found as 304.5, 367.5, 593, 148.0 and 258.0 mg g -1 of dry product, respectively. The extracts of SCL, SCR, SCB and SCK were markedly ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
3
34
2
Order By: Relevance
“…When mixed with other medicinal plants, the bark of S. birrea is employed to treat rheumatism and infectious diseases (Mojeremane and Tshwenyane 2004). The bark of S. birrea has also been reported to possess antioxidant activity (Mariod et al 2008). Previous studies revealed the anti-bacterial (Eloff 2001), anti-diabetic (Dimo et al 2007) and anti-convulsivant effect of the stem bark extracts of S. birrea (Ojewole 2007).…”
Section: Introductionmentioning
confidence: 97%
“…When mixed with other medicinal plants, the bark of S. birrea is employed to treat rheumatism and infectious diseases (Mojeremane and Tshwenyane 2004). The bark of S. birrea has also been reported to possess antioxidant activity (Mariod et al 2008). Previous studies revealed the anti-bacterial (Eloff 2001), anti-diabetic (Dimo et al 2007) and anti-convulsivant effect of the stem bark extracts of S. birrea (Ojewole 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The DPPH (1,1-Diphenyl-2-picrylhydrazyl) method was used to evaluate the antioxidant activity of the extracts. The DPPH radical has been widely used to test the free radical scavenging ability of different plants [20]. The DPPH scavenging activities of the extracts are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The powder Tetracera indica of 550 g was extracted with n-hexane solvent, ethyl acetate and ethanol respectively and after concentrated was obtained n-hexane extract 250 mg, ethyl acetate 3,50 g and ethanol extract 3.7 g. Each extract, has been done antioxidant activity test with varying concentration (Table 1). Mariod, Matthaus and Hussein, (2008) state that the value of antioxidant activity is determined based on the value of percentage inhibition, the higher the value of the inhibition, the higher the antioxidant activity. Table 1 showed that at the same concentration 1000 μg / mL, the ethanol extract showed the highest activity with inhibition 94.27% followed by ethyl acetate extract with inhibition 90.12%.…”
Section: Resultsmentioning
confidence: 99%